The complete mitochondrial genome of a non-biting midge Polypedilum unifascium (Tokunaga, 1938) (Diptera: Chironomidae) - Teng Lei; Chao Song; Xu-Dong Zhu; Bin-Ye Xu; Xin Qi (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial genome of Polypedilum unifascium (Diptera: Chironomidae) was determined by Illumina sequencing technology. The whole mitogenome is 16,452 bp in length with an A + T bias of 79.3%, and contains 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), and two ribosomal RNAs (rRNAs). All PCGs start with ATN codon and use TAA as the stop codon. Gene arrangement of the 13 PCGs is identical to that of other known Chironomidae mitochondrial genomes. The resultant Bayesian inference and maximum-likelihood trees based on the sequence data of 13 PCGs support its close relationship with P. vanderplanki.